THE INHIBITION TEST OF SECONDARY METABOLITES COMPOUNDS FROM ENDOPHYTE BACTERIA IN BANANA PEEL AGAINST PATHOGENIC BACTERIA AND FUNGI: ENDOPHYTE BACTERIA IN BANANA PEEL - Abbas, Sanatang; Yuliastri, Wa Ode; Rahul, Rahul (STIKes Mandala Waluya Kendari, 2025)
Background: The abundant banana production in Southeast Sulawesi causes environmental problems due to the large amount of banana peel waste. Banana peels contain nutrients that are food for microbes, especially endophytic bacteria. Endophytic bacteria from banana peels can produce secondary metabolite compounds that are used as agents to inhibit the growth of pathogenic bacteria and fungi. The purpose of this study was to determine the inhibitory power of secondary metabolite compounds from bacterial isolate code KPM2 (Kulit Pisang Mas 2) on bacteria and fungi. Methods: The inhibition zones of secondary metabolite compounds from bacterial isolate code KPM2 against Propionibacterium acne and Staphylococcus aureus bacteria were 14 mm and 12 mm, respectively, while the inhibition zones of Erythromycin and Cefoxitin were 28 mm and 17.5 mm, respectively. Results: The inhibition zone test of secondary metabolite compounds from KPM2 bacterial isolates against Aspergillus niger and Candida albicans fungi were obtained at 19.5 mm and 27 mm respectively, while the inhibition zone of Ketoconazole antifungal was 21.5 mm and 45 mm respectively. Conclusion: This study was concluded that the secondary metabolite compounds produced by KPM2 bacterial isolates were able to inhibit the growth of Propionibacterium acne and Staphylococcus aureus bacteria as well as on pathogenic fungi Aspergillus Niger and Candida albicans.